Analysis of The Role of Knowledge Sharing And Market Orientation On Business Performance (Study of Herbal Medicine SMEs in Kediri City) - Putri, Oktaria Ardika; Sri Hariyanti; Fudin, M. Ali; Halim, Steven (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
Now, Indonesia is one of the largest economies in the world, with substantial growth potential in the next few decades. To realize this potential, the Indonesian government has identified the important role of the SME sector in driving growth, creating jobs, and reducing poverty as is done by the Kediri City Government, in this case, the Department of Micro Business Cooperatives and Manpower, by sharing information and introducing markets to herbal medicine SMEs. This research uses a qualitative descriptive method to examine the role of knowledge sharing and market orientation carried out by the Kediri City Government to improve the performance of herbal medicine SME businesses. With interviews, documentation, and observations from this research, it can be concluded that knowledge sharing and market orientation have effectively improved the business performance of JAMU SMEs.